2013
DOI: 10.1039/c3sm50515d
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy non-linear excitations in sphere packings

Abstract: We study theoretically and numerically how hard frictionless particles in random packings can rearrange. We demonstrate the existence of two distinct unstable non-linear modes of rearrangement, both associated with the opening and the closing of contacts. Mode one, whose density is characterized by some exponent θ , corresponds to motions of particles extending throughout the entire system. Mode two, whose density is characterized by an exponent θ = θ , corresponds to the local buckling of a few particles. Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
259
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(287 citation statements)
references
References 49 publications
(189 reference statements)
24
259
3
1
Order By: Relevance
“…Its scaling with the distance to jamming does not match any scaling reported before for length scales of linear origin, such as l à or l c [4,11]. This suggests that r c could encompass crucial information about the density of the low energy nonlinear excitations reported recently for sphere packings [25]. Further insights in this matter could come from simulations of pointlike response of the kind reported in [7] albeit in the nonlinear regime.…”
Section: Prl 113 198001 (2014) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 89%
See 1 more Smart Citation
“…Its scaling with the distance to jamming does not match any scaling reported before for length scales of linear origin, such as l à or l c [4,11]. This suggests that r c could encompass crucial information about the density of the low energy nonlinear excitations reported recently for sphere packings [25]. Further insights in this matter could come from simulations of pointlike response of the kind reported in [7] albeit in the nonlinear regime.…”
Section: Prl 113 198001 (2014) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 89%
“…At finite shear strain amplitude γ, nonlinear effects become dominant [9,25,26] and the mechanical response of the system is no longer relevantly described exclusively by Δz. Finally, while dilatancy effects-namely, the increase of volume or pressure under shear-are important in sheared granular experiments [27][28][29], they are systematically missed in numerical and theoretical studies of soft spheres near jamming.…”
mentioning
confidence: 99%
“…Numerically it is found that θ e ≈ 0.44 both in two and three dimensions [32,33], suggesting that this quantity may be independent of dimension. Moreover, its value does not depend on the preparation protocol of the isostatic state: up to error bars, equal values are found from compression of hard spheres [32], shear-jammed hard disks [35], and decompression of soft spheres [33,36] 1 .…”
Section: Introductionmentioning
confidence: 94%
“…When an additional stress ratio is imposed to a marginal solid, naively one expects the contacts carrying [32,33]. In a packing only those contacts lead to plasticity when stress is increased, or when a shock (say a collision) occurs in the bulk of the material [32,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation